Agritourism Strategies in Tenganan Indigenous Environmental Stewardship : An Implementation of Community-Oriented Sustainable Tourism - Gede Yoga Kharisma Pradana; Gusti Ngurah Yoga Semadi; Derinta Entas; I Wayan Suadnyana (PT. Intelek Cendikiawan Nusantara, 2025)
This research aims to clarify how agritourism functions within environmental management in Tenganan, Karangasem. Customary environmental zoning primarily serves as a private realm for local cultural practices. Nonetheless, it has been shown that agritourism is incorporated into the zoning of the Tenganan traditional environment. The enquiries are 1) What are the attributes of Tenganan's traditional environmental management practices in Karangasem?; 2) What are the features of agritourism activities in the stewardship of Tenganan's customary environment in Karangasem ?; and 3) Is there cultural tolerance linked to agritourism activities within Tenganan's customary environmet in Karangasem? This study has been conducted utilising qualitative methodologies. Primary data was obtained by observation. Secondary data was acquired through a literature review. All data was analysed qualitatively-interpretatively with semiotics and a decolonization tourism approach. All data were subjected to qualitative analysis utilising a decolonizing tourism approach. The research findings indicate: 1) The Tenganan traditional environment in Karangasem is governed by cultural heritage, natural resources, and the residential areas of the Tenganan community; 2) Walking activities along designated routes amidst the natural ambience of plantations, agriculture, and forests exemplify agritourism within the Tenganan traditional environment; 3) Cultural tolerance exists within the Tenganan traditional environment regarding agritourism activities.